A two-step continuous synthesis of α-ketoamides and α-amino ketones from 2° benzylic alcohols using hydrogen peroxide as an economic and benign oxidant. Issue 30 (7th March 2016) - Liu, Chengkou; Fang, Zheng; Yang, Zhao; Li, Qingwen; Guo, Shiyu; Guo, Kai
Abstract : A practical two-step flow synthesis of α-ketoamides and α-amino ketones via direct oxidative coupling between 2° benzylic alcohols and amines was developed. Abstract : A practical two-step synthesis of α-ketoamides and α-amino ketones via direct oxidative coupling between 2° benzylic alcohols and amines was developed. Hydrogen peroxide, an economic and environmentally friendly oxidant, was used, and a metal catalyst was unnecessary. Moreover, the continuous-flow technique was employed to increase the functional group tolerance, efficiency and safety.